Pelatihan Bahasa Prancis Berbasis Media Audiovisual untuk Guru SMA dari 21 Kota di Indonesia - Baskoro, B. R. Suryo; Udasmoro, Wening; Andriani, Merry (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2022)
Audiovisual media-based French language training for high school teachers in Sumatra, Java and Eastern Indonesia aims to improve teachers’ abilities and provide access to audiovisual learning media especially for those serving in remote areas. French Literature Program FIB-UGM conducted it in collaboration with the French Embassy in Indonesia, Institut Français d’Indonésie, and TV5Monde. The success of socialization makes this program not only atrract high school teachers, but also by French lecturers from various universities and French teachers from five Institut Français d’Indonésie and Alliance Française. The program was conducted online and took place from 5 to 16 July 2021, followed by a total of 105 people. Participants were divided into 8 groups with a learning length of 27 hours / group. The training materials are divided into Modules A and B. Module A contains training on ‘exploring tv5monde.com sites for teachers’, ‘Accessing learning resources’, ‘using apprendre.tv5monde.com in the classroom’, and ‘understanding and using pedagogical tools on enseigner. tv5monde.com’. Module B contains everything in module A, ‘creating activities out of videos’, and ‘designing teaching sheets from audiovisual media’. This program provides access to teaching materials in the form of audio-visual documents that can be downloaded and used in classrooms that do not yet have adequate network infrastructure. This is an important contribution for teachers in the regions who often have difficulty accessing audio document teaching materials that suit the needs of their class. This training has been successfully improve the ability and confidence of high school and vocational teachers and produce output in the form of sitography (resources pages) databases easily accessible to teachers. ==== Pelatihan bahasa Prancis berbasis media audiovisual untuk guru SMA di Sumatra, Jawa, dan Indonesia Timur bertujuan untuk meningkatkan kemampuan guru dan memberikan akses media pembelajaran audiovisual, khususnya bagi mereka yang bertugas di daerah-daerah terpencil. Prodi Sastra Prancis FIB UGM melaksanakannya dengan bekerja sama dengan Kedubes Prancis di Indonesia, Institut Français d’Indonésie, dan TV5Monde. Keberhasilan sosialisasi membuat program ini tidak hanya diikuti oleh para guru SMA, tetapi juga oleh para dosen prodi Sastra Prancis dari berbagai perguruan tinggi dan para pengajar bahasa Prancis dari lima Institut Français d’Indonésie dan Alliance Française. Program dilaksanakan secara daring dan berlangsung pada 5—16 Juli 2021 dengan diikuti oleh total 105 orang. Peserta dibagi menjadi 8 kelompok dengan lama pembelajaran 27 jam/kelompok. Materi pelatihan dibagi ke dalam Modul A dan B. Modul A berisi pelatihan tentang ‘menjelajah situs tv5mode.com’, ‘mengakses sumber-sumber pembelajaran’, ‘menggunakan apprendre.tv5monde.com di kelas’, serta ‘memahami dan menggunakan lembar-lembar pedagogik pada enseigner.tv5monde.com’. Modul B berisi semua yang ada di modul A, ‘membuat kegiatan dari video’ dan ‘merancang lembar pengajaran dari media audiovisual’. Program ini memberikan akses bahan ajar berupa dokumen audiovisual yang dapat diunduh dan digunakan di kelas yang belum memiliki prasarana jaringan yang memadai. Hal ini menjadi kontribusi penting bagi guru-guru di daerah yang sering kali kesulitan mengakses bahan ajar dokumen audio yang sesuai dengan kebutuhan kelasnya. Pelatihan ini terpantau berhasil meningkatkan kemampuan dan kepercayaan diri para guru SMA dan SMK serta menghasilkan output berupa basis data sitografi yang mudah diakses oleh para guru.